1999
DOI: 10.1002/hep.510290317
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of endogenous nitric oxide during ischemia-reperfusion in the rat

Abstract: The aim of this study was to evaluate the protective or deleterious effects of endogenous nitric oxide (NO) on liver cells during hepatic ischemia-reperfusion (IR) in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
72
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 24 publications
8
72
0
4
Order By: Relevance
“…(42,43) In cardiomyocytes, hepatocytes, and endothelial cells, NO preconditioning was shown to have antiapoptotic effects in ischemia and reperfusion injury. (12) This study further showed that NO preconditioning produces antiapoptotic effects on oxidative stress-induced osteoblast apoptosis. Bcl-X L contributes to the protection of NO pretreatment from oxidative stress-induced apoptotic insults to osteoblasts.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…(42,43) In cardiomyocytes, hepatocytes, and endothelial cells, NO preconditioning was shown to have antiapoptotic effects in ischemia and reperfusion injury. (12) This study further showed that NO preconditioning produces antiapoptotic effects on oxidative stress-induced osteoblast apoptosis. Bcl-X L contributes to the protection of NO pretreatment from oxidative stress-induced apoptotic insults to osteoblasts.…”
Section: Discussionmentioning
confidence: 63%
“…(11) In ischemia and reperfusion injury, NO preconditioning was shown to produce protective effects on cardiomyocytes, hepatocytes, and endothelial cells. (12) Our previous studies showed that pretreatment with NO protects osteoblasts from oxidative stress-induced apoptotic insults via a mitochondriondependent mechanism. (8,13) Thus NO preconditioning may be applied as a cell model to investigate the survival signals or as an effective treatment of inflammation-induced bone diseases.…”
mentioning
confidence: 99%
“…40,41 Consistently, stimulation of NO production improves blood perfusion in preconditioned livers. 42 However, there is no indication that NO modulates hepatocyte response to hypoxia.…”
Section: Discussionmentioning
confidence: 82%
“…18,19 In ischemia and reperfusion injury, NO preconditioning was shown to produce protective effects on cardiomyocytes, hepatocytes, and endothelial cells. 20 It was suggested that NO is a mediator of estrogen action on bone in ovariectomized rats. 21 In this study, we used neonatal rat calvarial osteoblasts as the experimental model to evaluate the effects of the NO pretreatment on oxidative stress-induced cellular insults and the possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%